AB0932 Hypertrophic Cutaneous Lupus Erythematosus: A Diagnostic Pitfall. (10th June 2014) - Walsh, N.M.; Green, P.J.; Hanly, J.G.
Abstract : Background: Hypertrophic cutaneous lupus erythematosus (HCLE), an uncommon variant of discoid lupus erythematosus (DLE), is a challenging diagnosis. Its clinical presentation as verrucous nodules or markedly hyperkeratotic plaques on the extensor surfaces of the extremities and/or the face, and accompanying histopathological features simulate squamous cell carcinomas and actinic keratoses. Objectives: We studied our collective experience of this rare entity over the past decade, to establish whether existing awareness of its challenging nature is sufficient to avert medical error. Methods: Patients with HCLE were identified via clinical records in Rheumatology and Dermatology and cross referenced with those in Pathology. Demographic, clinical and pathological data were reviewed. Results: Seven patients [2 men and 5 women] with HCLE were identified. The mean age was 49 years (range 30-61). In 4 patients with systemic lupus erythematosus (SLE), 3 had previously documented DLE and were under the care of a dermatologist and/or a rheumatologist. The remaining 3 patients were managed by plastic surgeons. The hyperkeratotic nodules and plaques of HCLE were located on the face in 4 cases and on the extremities in 3. Biopsies were undertaken in 5 cases because of a clinical suspicion of malignancy and in 2 due to diagnostic uncertainty. In 3 patients an erroneous clinical and pathological diagnosis was made prior to recognition of HCLE: 2 were diagnosed with squamous cell carcinomas in the perioral area resulting in inappropriate surgery; the other was diagnosed with psoriasis. Conclusions: In this series from an academic medical centre there was a failure to recognize and appropriately treat HCLE in 3 of 7 patients upon initial presentation. Despite cautionary evidence in the literature, HCLE continues to elude diagnosis, thereby leading to delayed medical intervention or inappropriate surgery. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2260